Exploring Speaking Skill Challenges Faced by EFL Teachers in Primary and Secondary Education. - Alkharbash, Kholoud (Aljameai, 2025)
ABSTRACT :This study investigates the challenges faced by 32 English language teachers in Zawia, Libya, in teaching speaking skills. Utilizing a mixed-methods approach, the research combines questionnaires and semi-structured interviews to collect data on the difficulties teachers encounter in fostering oral communication among students. The findings reveal several key obstacles, including limited classroom resources, large class sizes, and insufficient student motivation. Additionally, teachers highlight a lack of professional training opportunities and challenges stemming from cultural and linguistic barriers. The study underscores the need for targeted teacher development programs, enhanced pedagogical strategies, and supportive educational policies to address these challenges. By providing actionable recommendations, this research aims to contribute to improving the teaching and learning of speaking skills in Libyan classrooms. المستخلص:  تُحقق هذه الدراسة في التحديات التي يواجهها 32 مدرسًا للغة الإنجليزية في مدينة الزاوية، ليبيا، أثناء تعليم مهارات التحدث. باستخدام منهجية مختلطة، تجمع الدراسة بين الاستبيانات والمقابلات شبه المنظمة لجمع البيانات حول الصعوبات التي يواجهها المدرسون في تعزيز مهارات التواصل الشفوي بين الطلاب. تكشف النتائج عن عدة عقبات رئيسية، بما في ذلك قلة الموارد التعليمية في الفصول، الكثافة العالية للصفوف، وضعف دافعية الطلاب. بالإضافة إلى ذلك، يسلط المدرسون الضوء على نقص فرص التدريب المهني والتحديات الناتجة عن الحواجز الثقافية واللغوية. تؤكد الدراسة على الحاجة إلى برامج تطوير مستهدفة للمعلمين، استراتيجيات تربوية محسنة، وسياسات تعليمية داعمة لمعالجة هذه التحديات. ومن خلال تقديم توصيات قابلة للتنفيذ، تهدف هذه الدراسة إلى المساهمة في تحسين تعليم وتعلم مهارات التحدث في الفصول الدراسية الليبية.